The Sandwich Generation: A Review of the Literature - LeaAnne DeRigne; Stephen Ferrante (University of North Florida, 2012)
Many Americans balance dual caregiving responsibilities for both children and aging family, dubbed the "sandwich generation." Between 1 out of8 and 1 out of11 households with an adult aged 30 or older is comprised of dual-earner, sandwiched generation couples. There are psychological, physical, employment, and financial outcomes ofbalancing multiple caregiving duties. The literature shows positive benefits for caregivers too. A review of literature in the past 30 years, citing only U.S.- based studies is summarized in this paper. Policy, clinical, and research implications are included. It is possible that multi- generational caregiving responsibilities will continue to rise for the children of baby boomers as life expectancies continue to go up, people continue to have children later in life, and continue to support those children to older ages. Policy and clinical sup- ports must be put into place to facilitate the highly necessary and valuable caregiving responsibilities ofthis population.